Petrography and geochemistry of distal spherules from the K–Pg boundary in the Umbria–Marche region (Italy) and their origin as fractional condensates and melts in the Chicxulub impact plume. (1st April 2017) - Belza, J.; Goderis, S.; Montanari, A.; Vanhaecke, F.; Claeys, P.
Abstract: The impact spherules from the distal K–Pg boundary sections are considered to represent silicate droplets condensed and solidified from a laterally expanding, cooling vapor plume formed upon hypervelocity impact. In the present-day Cretaceous–Paleogene boundary (K–Pg) spherule population of the Umbria–Marche region in Italy, three texturally and compositionally distinct types of impact spherules can be identified that are dominantly composed of (1) goethite, (2) K-feldspar or (3) glauconite. Although these phases represent the products of diagenetic alteration, the remnant textural characteristics of the spherules and the type of alteration product are indicative of the spherules' original compositions, which are important to constrain the physicochemical conditions prevalent throughout the impact vapor plume. The presence of relict ghost crystals and the identification of 'iddingsite' indicate that goethite likely represents pseudomorphic replacement after olivine. Goethite spherules contain numerous dendritic, euhedral and skeletal spinel crystals variably dispersed in the groundmass. In terms of textures, five types of goethite spherules can be distinguished, showing striking similarities to chondrules: (I) skeletal, (II) barred, (III) radial/barred, (IV) porphyritic and (V) relict/granular. The morphology of both spinel and olivine (pseudomorphs) is consistent with established formation conditions (peak temperature T max, degree of supercooling Δ T, cooling rate, presence of nucleation sites) for different chondrule textural types. As goethite spherules are anomalously enriched in moderately to highly refractory lithophile (Sc, V, Y, Zr, Nb, REE, Hf, Ta, Th) and siderophile (Cr, Co, Ni, W, Ir, Pt) elements, they are interpreted to represent (diagenetically altered) refractory (high- T ) condensation products from a well-homogenized plume consisting of both vaporized target and projectile matter. Different from goethite spherules, K-feldspar spherules exhibit pseudomorphic textures after lower-liquidus silicates such as Ca-rich pyroxene and plagioclase. Furthermore, the K-feldspar spherules yield systematically lower abundances of the most refractory trace elements. This suggests that the pre-altered K-feldspar spherules are part of the same fractional condensation sequence of the target-impactor vapor plume, cooled during lateral expansion. Glauconite spherules are cryptocrystalline, exhibiting hemispherical lamellae that resemble the palagonite/smectite alteration layers of basaltic glasses and the K–Pg spherules (microtektites) found at proximal sites around the Gulf of Mexico region. Their trace element contents and REE patterns are strikingly similarity to those of (altered) K–Pg microtektites, suggesting that glauconite spherules represent former glass spherules without crystallites/microlites. Glauconite spherules are interpreted not to be part of the fractional condensation sequence of the impact vapor plume that led to the formation of the replaced goethite and K-felspar spherules. They were likely formed by entrainment of melt, expelled at the steepest angles and highest ejection velocities from the central melt sheet, within the edges of the vapor plume. This work is the first to create a geochemical foundation for vapor plume models, both at the major and trace element scale. In addition, it highlights the unique characteristics of the Chicxulub impact event and emphasizes the importance of its unusual target lithologies. The heterogeneous, layered, and volatile-rich target contributed significantly to the formation of a dust-rich environment, high oxygen fugacities and the preservation of some degree of heterogeneity in the vapor plume. In addition, striking similarities between distal (goethite-type) K–Pg spherules and chondrules may argue for a reevaluation of the impact model as a possible origin for the formation of certain types of cosmic chondrules.